Legal Protection for Foreign Investment According to Law Number 25 of 2007 concerning Investment - Marbun, Putra Hasian; Nababan, Roida; Gultom, Meli Hertati (PT FORMOSA CENDEKIA GLOBAL, 2025)
This writing aims to explore the importance of a legal regulation that is able to provide legal protection for foreign investment. Foreign investment is a very important instrument for the development of the nation's economy so that a legal regulation is needed to provide legal certainty for foreign investors so that they feel safe and comfortable in carrying out investment practices in Indonesia. In this study, the author will focus on exploring How Legal Protection for Foreign Investment is According to Law Number 25 of 2007 Concerning Investment and What Forms of Ease of Land Rights Licensing Services Are According to Law Number 25 of 2007 Concerning Investment. The data collection method in this study was carried out through library research and document review, namely by collecting legal materials through studies of journals, legal research results, and various official institutional documents such as laws and regulations, trial circulars, and other literature relevant to the problems studied.